THE ROLE OF PRIVATE QURAN LESSONS IN FORMING ISLAMIC CHARACTER - Tutun Usman, Asep; Muhammad Taufiq, Fardan; Ahmad Saduloh, Idad; Farid, Moh Rizaluddin (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This study analyzes the role of private Quran lessons in shaping Islamic character through the Systematic Literature Review approach with the stages of theme determination, reference search, literature selection, analysis and interpretation, drafting, and denomination of results. The focus of the study in this study is on 4 things, the role of private lessons, private Quran lessons learning, private Quran lessons methods, and the formation of Islamic character. The results of the study indicate that private Quran lessons are effective in shaping Islamic character by using the sorogan, classical-individual and habituation methods, thus facilitating the understanding of Islamic law and its application in everyday life.